Suomalaisia vaikuttajanaisia : kohti vuotta 2000 - Sievänen-Allen, Ritva; Bélinki, Karmela (WSOY, 1998)
Summary: The influential Finnish woman.
Keywords: Aarikka, Kaija; Arajärvi, Terttu; Bandler, Vivica; Forssell, Kyllikki; Haavio-Mannila, Elina; Hetemäki-Olander, Elsi; Hiltunen, Eila; Hämäläinen, Sirkka; Kilpi, Eeva; Palotie, Leena; Raittila, Anna-Maija; Rehn, Elisabeth; Setälä, Päivi; Sipilä, Helvi; Sollamo, Raija; Tiivola, Satu; Tikkanen, Märta; Uosukainen, Riitta; Volanen, Eeva-Kaarina; Väänänen, Marjatta; naiset : urakehitys; elämäkerrat : naiset